2015
DOI: 10.1007/s10841-015-9824-z
|View full text |Cite
|
Sign up to set email alerts
|

Positive effects of ecological restoration on rare and threatened flat bugs (Heteroptera: Aradidae)

Abstract: Intensive management of boreal forests has replaced natural disturbances, leading to losses of residual deadwood and saproxylic biodiversity. Declining population sizes have been well documented for insect groups such as bark and wood-boring beetles, whilst other groups such as flat bugs (Heteroptera: Aradidae) are less wellstudied and little is known about their response to forest restoration. We conducted two restoration experiments addressing this lack of knowledge. We predicted the following responses to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…The project is representative of LIFE projects targeted to forest and peatland restoration in Finland. Information on the project was compiled from scientific ,b, Similä et al 2014, Hägglund et al 2015, Tarvainen and Tolvanen 2015 and public papers Junninen 2012, Similä et al 2014), project proposals, restoration plans, maps, and practical experiences.…”
Section: Figmentioning
confidence: 99%
“…The project is representative of LIFE projects targeted to forest and peatland restoration in Finland. Information on the project was compiled from scientific ,b, Similä et al 2014, Hägglund et al 2015, Tarvainen and Tolvanen 2015 and public papers Junninen 2012, Similä et al 2014), project proposals, restoration plans, maps, and practical experiences.…”
Section: Figmentioning
confidence: 99%
“…It is listed as vulnerable in the Red Lists of Sweden and Finland (Gärden-fors 2000, Rassi et al 2001). In Sweden and Finland the species has been found on charred tree trunks up to three years after forest fires (Helioevaara and Vaisanen 1983, Pettersson and Nilsson 1986, Heiss and Péricart 2007, Hagglund et al 2015, Heikkala et al 2017 (Fig. 4) and Heiss & Baena, 2006 (red, n=7) in Europe, and new records of both species in Switzerland (star).…”
Section: Discussionmentioning
confidence: 97%
“…coll. MMG) and the website of the Muséum national d'histoire naturelle Paris (https://science.mnhn.fr/institution/mnhn/collection/eh/item/eh18974?lang=en_US) for Q. marcosi and Reuter (1900), Helioevaara and Vaisanen (1983), Pettersson and Nilsson (1986), Lammes and Rinne (1990), Roth and Coulianos (2014), Hagglund et al (2015), Heikkala et al (2017), Heikkala (pers. com.…”
Section: Discussionmentioning
confidence: 99%
“…Other taxa Short-term effects of retention Johansson et al (2010) and Hägglund et al (2015) detected an overall increase of flat bugs (Heteroptera: Aradidae) following gap harvesting in Swedish spruce forests. Heikkala et al (2017) found that retention in pine-forest clear cuts supports these species (Table 2).…”
Section: Other Aspectsmentioning
confidence: 99%